The effect on color and dimensional stability of heat cured acrylic resin denture base after being immersed in chocolate and tea drinks - Supramaniam, Nithiakala; Putranti, Dwi Tjahyaning (Indonesia Prosthodontic Association, 2021)
The denture base is an important part because it acts as a support for the tissue around the tooth. Optimal support and aesthetic result in the manufacture of denture bases require several considerations. Color and dimensional sta- bility are one of the important factors for denture bases. In this experimental laboratory study, the denture base was immersed in chocolate and tea drinks and measured the color and dimensional stability before and after immersing. Colorimeter is used as a measurement device for color stability and digital calipers as a measurement device for dimensional stability. The mean differences in color and base dimensions of the dentures were tabulated and the Kruskal-Wallis test was used to analyze them. The results showed that there were very high differences in color and dimensions of immersing tea drinks